THE PLACE OF PHILOSOPHY TODAY - Rios Alves Nunes da Costa, Marta (2022)
In this article I aim at identifying the role of philosophy in the contemporary world. In the first section, I clarify the meanings of philosophy. Making a short digression on the evolution of philosophy since the Greeks until today. From a practical and existential attitude to a logic of compartimentalization of knowledge I ask the question: How can one teach and learn philosophy?  In the second section I look into its purpose by reflecting upon the role of the philosopher and philosophy professor having as starting point a dialogue with Rancière’s Ignorant Master. Finally, I try to identify the role of philosophy today. In order to do so, I revisit the relationship between philosophy and truth. Starting with a dialogue with Heidegger, Aristotle, Kant and Heath I show how philosophy remains of crucial importance for contemporary days, however, I argue that philosophy’s importance and role today depends on the recovery of its commitment with Truth, wisdom and (non-dogmatic) critique.